2016
DOI: 10.1371/journal.pone.0150175
|View full text |Cite
|
Sign up to set email alerts
|

Solar Simulated Ultraviolet Radiation Induces Global Histone Hypoacetylation in Human Keratinocytes

Abstract: Ultraviolet radiation (UVR) from sunlight is the primary effector of skin DNA damage. Chromatin remodeling and histone post-translational modification (PTM) are critical factors in repairing DNA damage and maintaining genomic integrity, however, the dynamic changes of histone marks in response to solar UVR are not well characterized. Here we report global changes in histone PTMs induced by solar simulated UVR (ssUVR). A decrease in lysine acetylation of histones H3 and H4, particularly at positions of H3 lysin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Our previous study demonstrated a massive reduction of histone lysine acetylation in human keratinocytes exposed to ssUVR 24 . As histone acetylation is normally associated with active gene expression, it is quite surprising that the numbers of up-regulated and down-related genes are equally represented in most comparison conducted in our study, with the exception of cells exposed to repetitive ssUVR at 3 J/cm 2 .…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Our previous study demonstrated a massive reduction of histone lysine acetylation in human keratinocytes exposed to ssUVR 24 . As histone acetylation is normally associated with active gene expression, it is quite surprising that the numbers of up-regulated and down-related genes are equally represented in most comparison conducted in our study, with the exception of cells exposed to repetitive ssUVR at 3 J/cm 2 .…”
Section: Discussionmentioning
confidence: 89%
“…The range of doses used in the study is comparable to what a person would be exposed to when standing outside for 40 minutes (3 J/cm 2 ) to 2.5 hours (12 J/cm 2 ) at noon under a clear sky with a UV index of 6 or higher 24 . Our previous study found that HaCaT cells exposed to a single dose of 12 J/cm 2 exhibited a moderate increase of phosphorylated histone variant H2AX, a well-characterized marker of DNA damage, at 1 hour post irradiation, as well as limited cell death (less than 20%) at 24 hours after irradiation 24 . Irradiated cells were harvested 24 hours post irradiation and subjected to transcriptional profiling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon further analysis, UV-induced differential H3K27ac acetylation was functionally correlated with differential gene expression was observed [76]. The genome wide loss of H3K27ac may be attributable to the suppression of histone acetyltransferases activities, whereas the regional gain of H3K27ac may occur secondary to the binding of UV-responsive transcription factors, such as JUN/FOS or TP53, which subsequently recruit HATs to their target regions [76,77]. Though the epigenetic mechanisms underlying the effects of UVR in promoting skin cancer warrant more extensive studies, the use of histone biomarkers for clinical diagnosis and/or prognosis is an interesting approach that is also being investigated for use in other malignancies [78,79].…”
Section: Epigenetic Alterationsmentioning
confidence: 99%